Levantamento Bibliográfico sobre Educação Especial e Ensino de Ciências no Brasil - Silva, Larissa Vendramini Da; Bego, Amadeu Moura (Associação Brasileira de Pesquisadores em Educação Especial - ABPEE, 2018)
ABSTRACT: With the World Declaration of Education for All, Brazil has opted to build an inclusive education system. Thus, it is necessary that Special Education is also the subject of research on Teaching Science, but studies indicate that there is little research in this area. As such, the aim of this work was to carry out a national bibliographical survey to evaluate how the research area of teaching Science has approached the Special Education theme. The bibliographic research was carried out in line with the revision procedures defined by Content Analysis and used six journals of strata A1 and A2 defined by CAPES qualis as corpus of information. The searches were carried out from five descriptors: inclusion, inclusive education, special education, special educational needs and teacher education. According to the selection criteria, only 28 papers were found: 15 on teaching Science and learning; 12 on the education of Science teachers from the perspective of Special Education and one on evaluation and curriculum for Special Education. Most of these works were written by Éder Pires de Camargo and Anna Maria Canavarro Benite, and the teaching of Physics for the visually impaired is the theme that has been published the most. The publications began in 2006, reaching the largest number of publications in 2015. The results show that the amount of research in this area is still incipient, having little representation compared to the total number of publications in the best evaluated journals.

RESUMO: Com a Declaração Mundial de Educação para Todos, o Brasil optou por construir um sistema de educação inclusivo. Desse modo, é necessário que a Educação Especial seja também objeto de pesquisa sobre o Ensino de Ciências, mas estudos indicam que há pouca pesquisa na área. Assim sendo, o objetivo deste trabalho foi realizar um levantamento bibliográfico nacional e avaliar como a área de pesquisa em ensino de Ciências tem abordado a temática Educação Especial. A pesquisa bibliográfica foi realizada por meio dos procedimentos de revisão definidos pela Análise de Conteúdo e utilizou como corpus de informação seis periódicos acadêmico-científicos de estratos A1 e A2 definidos pelo qualis da CAPES. As buscas foram realizadas a partir de cinco descritores: inclusão, educação inclusiva, educação especial, necessidades educacionais especiais e formação de professores. Em função dos critérios de seleção, foram encontrados apenas 28 artigos: 15 sobre ensino e aprendizagem de Ciências; 12 sobre formação de professores de ciências na perspectiva da educação especial e 1 sobre avaliação e currículo para a Educação Especial. Esses trabalhos, em sua maioria, foram escritos por Éder Pires de Camargo e Anna Maria Canavarro Benite, e o ensino de Física para deficientes visuais é a temática que mais tem sido publicada. As publicações tiveram início em 2006, com o maior número de publicações em 2015. Conclui-se que ainda é incipiente o número de pesquisas na área, possuindo pouca representatividade frente ao total de publicações nas revistas mais bem avaliadas da área.
Bibliographical Survey on Special Education and Teaching Science in Brazil
Keywords: Teaching Science; Special Education; Bibliographic survey; Ensino de Ciências; Educação Especial; Levantamento bibliográfico